2020
DOI: 10.21203/rs.3.rs-98496/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of fungal oligosaccharide-oxidising flavo-enzymes with previously unknown substrates, redox-activity profiles and interplay with LPMOs

Abstract: Oxidative plant cell-wall processing enzymes are of great importance in biology and biotechnology. Yet, our insight into the functional interplay amongst such oxidative enzymes remains limited. Here, a phylogenetic analysis of the auxiliary activity 7 family (AA7), currently harbouring oligosaccharide flavo-oxidases, revealed a striking abundance of AA7-genes in phytopathogenic fungi and Oomycetes. Expression of five fungal enzymes, including three from unexplored clades, expanded the AA7-substrate range and u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Homologs of AA7 were found in plants, fungi and fungi-like microorganisms. A huge abundance of AA7 genes was revealed in phytopathogenic fungi and Oomycota [38]. We also observed an increased occurrence of AA7 homologs in saprotrophic and entomopathogenic fungi.…”
Section: Cazymes With Auxiliary Activity (Aa)supporting
confidence: 53%
See 1 more Smart Citation
“…Homologs of AA7 were found in plants, fungi and fungi-like microorganisms. A huge abundance of AA7 genes was revealed in phytopathogenic fungi and Oomycota [38]. We also observed an increased occurrence of AA7 homologs in saprotrophic and entomopathogenic fungi.…”
Section: Cazymes With Auxiliary Activity (Aa)supporting
confidence: 53%
“…The AA7 family harbours oligosaccharide flavo-oxidases which can transfer electrons to lytic polysaccharide monooxygenase and, consequently, fuel cellulose degradation [38]. Homologs of AA7 were found in plants, fungi and fungi-like microorganisms.…”
Section: Cazymes With Auxiliary Activity (Aa)mentioning
confidence: 99%
“…However, in a preprint in 2016 (eventually published in 2017 (Bissaro et al ., 2017)), Bissaro and colleagues demonstrated the occurrence of an efficient peroxygenase reaction (Bissaro et al ., 2017), that is using H 2 O 2 rather than O 2 . At this time, multiple kinetics studies have shown that both apparent affinity and catalytic efficiency are several orders of magnitude higher for H 2 O 2 (Hangasky et al ., 2018; Kuusk et al ., 2018, 2019; Bissaro et al ., 2020a; Hedison et al ., 2020; Jones et al ., 2020; Kont et al ., 2020; Momeni et al ., 2021). This conclusion is further supported by synergistic studies with H 2 O 2 ‐producing redox partners (Bissaro et al ., 2017; Hegnar et al ., 2019; Kracher et al ., 2020; Momeni et al ., 2021).…”
Section: The Bumpy Road Of Lpmo Researchmentioning
confidence: 99%
“…At this time, multiple kinetics studies have shown that both apparent affinity and catalytic efficiency are several orders of magnitude higher for H 2 O 2 (Hangasky et al ., 2018; Kuusk et al ., 2018, 2019; Bissaro et al ., 2020a; Hedison et al ., 2020; Jones et al ., 2020; Kont et al ., 2020; Momeni et al ., 2021). This conclusion is further supported by synergistic studies with H 2 O 2 ‐producing redox partners (Bissaro et al ., 2017; Hegnar et al ., 2019; Kracher et al ., 2020; Momeni et al ., 2021). However, there is the possibility that the actual mechanistic path depends on the biological context and substrate/cosubstrate availability.…”
Section: The Bumpy Road Of Lpmo Researchmentioning
confidence: 99%
See 1 more Smart Citation